A review of geothermal energy resources, development, and applications in China: Current status and prospects. (15th December 2015) - Zhu, Jialing; Hu, Kaiyong; Lu, Xinli; Huang, Xiaoxue; Liu, Ketao; Wu, Xiujie
Abstract: The objective of this paper is to introduce geothermal energy resources, utilization, development roadmap, and government support in China. Over the last 20 years, China was the first place in the world in direct utilization of geothermal energy with total amount reaching 17, 870 MWt in 2014, and with an increasing trend annually. Compared with the rapid increase of direct utilization, the development of geothermal power generation in China is not obvious in the past 40 years, with an installed capacity of 27.78 MWe, ranking 18th in the world at present. It is reported that geothermal heating area was up to 396 million square meters with an installed capacity of 1178 MWt in 2013. Research on HDR (hot dry rock) resources is in its infancy. Considering the recoverable coefficient of 2%, energy stored in HDR at a depth of 3.0–10.0 km is 4500 times the total energy consumption in China in 2013. In order to achieve sustainable development of geothermal energy in China, attention should be paid to the following aspects in the future: technology development of EGS (enhanced geothermal system), low cost and scale-up of geothermal power generation, cascade utilization in geothermal heating, and sustainable exploitation and utilization of geothermal reservoirs. Highlights: Geothermal resources in China are presented. Different utilizations of geothermal energy in China are summarized. Research on the exploitation and utilization of geothermal energy in China is reviewed. Roadmaps of exploitation and development of geothermal energy in China are presented. Government support for geothermal exploitation and R&D in China is overviewed.